THE DEVELOPMENT OF RADICAL ISLAMIC MOVEMENTS AND THE IMPORTANCE OF ANTI-RADICALISM EDUCATION AT THE HIGH SCHOOL LEVEL IN INDONESIA - Leilana Octaviani; Dewi Nur Indah Sari; Ahmad Fauzan Hidayatullah (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
Radicalism is a challenge and concern for the world, including the Muslim community in Indonesia. The radicalism movement is evidenced by the existence of violence in achieving its goals in political, religious, social, educational, and economic matters. In the world of education in Indonesia, violence, and intimidation still often occurs so that anti-radicalism education is needed which can be realized through the teaching process, especially at the high school level. Anti-radicalism education requires humans to respect each other's differences and make peace according to the Al-Quran and Hadith guidelines which are integrated through education. For this reason, the analysis in this article is descriptive qualitative with an approach using the library method which aims to understand the history of the development of the Islamic radicalism movement and Islamic solutions to overcome the problems of religious radicalism and terrorism by implementing anti-radicalism education. Besides, this article will describe some of the terminology and examples of the influence of the Islamic radical movement at the senior high school. In Indonesia, the emergence of Islamic radicalism is based on three factors, namely developments at the global level, namely the radical group from the Middle Eastern. Second, the widespread of Wahhabi has led to conflict. And the third is poverty. The field of education also has an impact on Islamic radicalism, which can be from teachers to students, the influence of technological sophistication, the influence of Wahhabi understanding, poverty, even the materials in student worksheets and books also contain many radical values. Therefore, anti-radicalism education is very important because it can require the younger generation to respect differences, humans who love compassion, and humans who hate doing damage. Efforts to overcome radicalism at high school levels can be done with character education